Key Factors Analysis of Customer Satisfaction of Marketplaces in Batam City - Yulianti, Yulianti; Christiarini, Renny (https://jurnal.binamandiri.ac.id/, 2023)
This study aims to analyze customer satisfaction in the city of Batam. The data collected in this study were 400 respondents. This study uses primary data using an online questionnaire (google form). Respondents are Batam residents who use the marketplace. The sampling method used is non-probability sampling. This research uses a quantitative analysis method. This study uses the Partial Least Squares (PLS) methods with SPSS Statistics. The study results are Shopee (Indonesia) and Taobao (China) are the most widely used marketplaces in Batam. E-Service quality, brand image, price, product quality, and trust significantly influence a purchase decision. In addition, price, product quality, and trust significantly affect customer satisfaction. Although e-service quality and brand image are not determinants in the satisfaction felt by marketplace users, they are the basis for consumer observations and decisions when buying the desired product.